TEMPAT PENGOLAHAN SAMPAH TERPADU (TPST) URGENSI DAN IMPLEMENTASINYA - Firman L. Sahwan (BPPT)
TPA is the main priority in handling municipal solid waste in Indonesia, with many problems and challenges. TPST is one of other alternatives in handling solid waste in accordance with Solid Waste Management Law No. 18 year 2008, therefore it has an important role in reducing heavy burden of TPA. Activities that can be done in TPST are collecting, sorting, re-using, re-cycling, treatment of fi nal processing, either for organic solid waste or for inorganic solid waste. However, based on characteristic of municipal waste, it’s better the stressing activities are pointed to organic solid waste treatment that make composting as the main alternative activity. Government support and help are much needed in order that TPST activity can be optimally done.Keywords : municipal solid waste, integrated treatment facility, composting